Experimental investigation into the functionality of alkaline water electrolysis with ion-solvating membrane in anode feed mode using diluted potassium hydroxide - Dieter Jarosch; John James Warren; Jörg Kapischke (Heliyon)
This study explores the unique operating behavior of an alkaline water electrolysis cell equipped with an ion-solvating membrane, operated with a diluted alkaline electrolyte, specifically 1-M potassium hydroxide (1M KOH), in anode feed mode. Our investigations reveal several key insights. Charge transport: In an ion-solvating membrane, charge transport occurs through both the cations and anions of the electrolyte. Due to electro-osmosis, cation transport to the cathode results in a combined hydrogen-electrolyte discharge from the cathode compartment of the electrolysis cell. The discharged electrolyte is more concentrated than the electrolyte supplied to the anode. The concentration and flow rate of the electrolyte increase with current density and electrolyte temperature. Current density dependence: Since only a fraction of the total charge is transferred by hydroxide ions within the membrane, current density strongly depends on the electrolyte flow through the anode compartment. Membrane stability and performance: The membrane's mechanical and chemical stability enables operation at high temperatures, up to 80 °C. This stability enables increased current density at a given cell voltage. Effects of catalyst use: Using cathode catalysts with high surface areas, such as Raney-Ni, enhances current density because highly concentrated liquid potassium hydroxide forms at the cathode during operation. Anode catalysts with high surface areas increase current density, but only if the flow of hydroxide ions is not impeded. Otherwise, the jV-curve exhibits transport-limited behavior.